Subtherapeutic concentrations of infliximab and adalimumab are associated with increased disease activity in Crohn's disease. (13th March 2018) - Carlsen, Arne; Omdal, Roald; Leitao, Kristian Øgreid; Isaksen, Kjetil; Hetta, Anne Kristine; Karlsen, Lars Normann; Aabakken, Lars; Bolstad, Nils; Warren, David; Lundin, Knut E.A.; Grimstad, Tore
Background: Low anti-tumor necrosis factor α (TNFα) serum concentrations may result in lack of treatment response in patients with inflammatory bowel disease. We determined the anti-TNFα drug concentrations in patients with inflammatory bowel disease and investigated whether or not subtherapeutic drug concentrations were associated with increased levels of disease activity. Methods: In a single-center cross-sectional study, we included patients with ulcerative colitis or Crohn's disease who were receiving infliximab or adalimumab maintenance therapy. Demographic data, disease activity symptom scores (Partial Mayo Score, Harvey Bradshaw Index), inflammatory markers [C-reactive protein (CRP), fecal calprotectin], antidrug antibodies and serum drug concentrations were recorded. Therapeutic drug concentrations were defined as 3–8 mg/liter for infliximab and 5–12 mg/liter for adalimumab. Results: Of 210 patients included, 137 (65.2%) had Crohn's disease. In the adalimumab group, subtherapeutic drug concentrations were measured in 16.7% of patients with ulcerative colitis and in 27.7% of patients with Crohn's disease. In the infliximab group, subtherapeutic drug concentrations were found in 23% (ulcerative colitis) and 30.3% (Crohn's disease) of patients. In Crohn's disease, subtherapeutic adalimumab concentrations were associated with higher fecal calprotectin and CRP concentrations compared with therapeutic concentrations. Subtherapeutic infliximab concentrations in patients with Crohn's disease were also associated with higher CRP concentrations compared with therapeutic concentrations. Conclusions: The prevalence of subtherapeutic drug levels ranged from 17% to 30%. In patients with Crohn's disease, subtherapeutic serum drug concentrations were associated with significantly higher disease activity with both anti-TNFα agents. These findings were not observed in patients with ulcerative colitis. Clinicaltrials.gov identifier [NCT02134054]